HPLC‐MS and UV–Visible Coupled Analysis of Methylene Blue Photodegradation by Hydrothermally Grown ZnO Nanowires. Issue 24 (23rd October 2021) - Martin, Nathan; Leprince-Wang, Yamin
Abstract : Photocatalysis is an efficient and promising method to purify water. Numerous studies have been dedicated to demonstrate its efficiency on several hazardous compounds, derived from various industries. However, even if the degradation of such products has been extensively studied, obtaining information on their photodegradation pathway is still challenging, leading to concerns about the innocuousness of the treated water. In this study, the authors use ZnO nanowires (ZnO NWs), to photodegrade a solution of the commonly used organic dye methylene blue (MB) under ultraviolet (UV) irradiation, followed simultaneously by UV‐visible (UV‐vis) spectrometry and high‐performance liquid chromatography coupled with mass spectrometry (HPLC‐MS). Combining these two methods real‐time information on the photodegradation efficiency and degradation mechanism are given. The HPLC‐MS analysis allows us to confidently identify three reaction intermediates of the MB degradation: Azure A, B and C, as well as spot three other compounds, with uncertain formulas, leading to the presented hypothesis on the beginning of the MB degradation pathway. While the UV‐visible analysis shows a total degradation of MB after 2 h of photodegradation, the HPLC‐MS analysis indicates that some MB remain in the solution. Its quantity is calculated to be 14 μg L −1, which is harmless to humans. Abstract : By combining ultraviolet‐visible (UV‐vis) spectrometry and high‐performance liquid chromatography (HPLC) coupled with mass spectrometry (MS), the efficiency of hydrothermally grown ZnO nanowires for the photocatalytic degradation of methylene blue to harmless concentrations under UV light is demonstrated, and an informed hypothesis on the degradation mechanism is established.